About the Social Dimension of Forgiveness and the Possibility of Reconsidering it as a Reconciliation Process with Harm - Molina González, Liliana C. (Estudios de Filosofía, 2016)
The aim of the article is questioning the moral dimension of forgiveness in the context of harm related to the armed conflict in Colombia. It is troublesome though to consider forgiveness only as forgiving harm, giving up resentment or reconciling with the offender. This article proposes to consider forgiveness as a moral response related to other feelings or moral responses to harm and as a consistent process in reconciliation, digestion and absorption of harm. This will emphasize the social dimension of the process and will also show that, as a process of reconciliation with the costs of harm, forgiveness involves a moral sanction and does not exclude the possibility to claim for suffered harm.